Multibiomarker approach to fipronil exposure in the fish Dicentrarchus labrax under two temperature regimes - Dallares, Sara (2020)
Fipronil is a phenylpyrazole insecticide widely used to control pests in agriculture even though evidence of harmful side effects in non-target species has been reported. A comprehensive study on the effects of dietary administration of Regent (R) 800WG (80 % fipronil) in European sea bass juveniles was carried out under two temperature regimes: a) natural conditions, and b) 3 degrees C above the natural temperature (an increase predicted for the NW Mediterranean by the end of this century). Fipronil was added to the fish food (10 mg fipronil /Kg feed) and the effects were studied at several time points including right before administration, 7 and 14 days after daily fipronil feed and one-week after the insecticide withdrawal from the diet (depuration period). A wide array of physiological and metabolic biomarkers including feeding rate, general condition indices, plasma and epidermal mucus metabolites, immune response, osmoregulation, detoxification and oxidative-stress markers and digestive enzymes were assessed. General linear models and principal component analyses indicated that regardless of water temperature, fipronil resulted in a significant alteration of several of the above listed biomarkers. Among them, glucose and lactate levels increased in plasma and decreased in epidermal mucus as indicators of a stress response. Similarly, a depletion in catalase activity and higher lipid peroxidation in liver of fipronil-exposed fish were also indicative of an oxidative-stress condition. Fipronil induced a time dependent inhibition of Cytochrome P450-related activities and an increase of phase II glutathione-S-transferase. Moreover, fipronil administration was able to reduce the hypo-osmoregulatory capability as shown by the increase of plasmatic osmolality and altered several digestive enzymes including trypsin, lipase, alpha amylase and maltase. Finally, analyses in bile and muscle confirmed the rapid clearance of fipronil but the persistence of the metabolite fipronil-sulfone in bile even after the 7-day depuration period. Altogether, the results reveal a notable impact of this compound on the physiological condition of the European sea bass. The results should be considered in future environmental risk assessment studies since fipronil could be hazardous to fish species, particularly those inhabiting estuarine ecosystems exposed to the discharge of agriculture runoffs where this pesticide is mainly used.